ASEAN - Severino, Rodolfo (Book collections on Project MUSE., 2008)
Describes the Association of Southeast Asian Nations and the impact it has had on the region. Discusses how it helped bring peace and stability to the region and has successfully engaged the world's major powers, in East Asia and beyond.